Retrobulbar Neuritis: Rare Presentation in Dengue Fever - Atul Bhasin; R. K. Singal; Atul Prasad; Rahul Handa; Harsh Mittal (Indian Journal of Medical Specialities)
Dengue fever is transmitted by the bite of infected female Aedes aegypti mosquito. There has been a worldwide resurgence of disease over the past few decades. Southeast Asia, American tropics, and subtropical countries have seen many epidemics in recent past, with the annual incidence of disease exceeding 50–100 million per year. Dengue fever is characterized by fever, malaise, headache, muscle ache, retro-orbital pain, purpuric rash, and bleeding diathesis due to thrombocytopenia. Neurological symptoms have been reported as changing clinical profile of dengue infection. Encephalopathy and encephalitis are being increasingly reported other than hemorrhagic cerebrovascular presentations. Ophthalmic complications involving the anterior and posterior chambers have been reported with varying incidence. Blurring of vision, scotoma, retinal hemorrhages, macular edema, and optic neuropathy have also been reported. We report here a rare case of retrobulbar optic neuritis in a case of dengue fever which showed complete recovery from ocular symptoms on recovering from dengue fever.